Effect of hydrogen adsorption to the high strength steel in soil aqueous environment - Muhammad Faez Helmie, Mohd Suhaimi (2013)
This thesis is carried out to investigate the effect of hydrogen adsorption to the high strength steel in soil aqueous environment. This study is about how hydrogen adsorption in soil aqueous environment will affect the material appearance and loss of weight will be used to determine the corrosion rate. This study is using three different concentration of H2SO4 to add in the soil; 2 ml, 4 ml and 6 ml and H2O. Increasing H2SO4 concentration promoted higher corrosion rate and higher loss of weight. Under the tested condition it was found that the higher concentration of H2SO4 led to a higher corrosion rate and higher loss of weight. It is concluded that by increasing H2SO4 concentration leads to the increasing of corrosion rate.